Istaroxime, a positive inotropic agent devoid of proarrhythmic properties in sensitive chronic atrioventricular block dogs. (July 2018) - Bossu, Alexandre; Kostense, Amée; Beekman, Henriette D.M.; Houtman, Marien J.C.; van der Heyden, Marcel A.G.; Vos, Marc A.
Graphical abstract: Abstract: Current inotropic agents in heart failure therapy associate with low benefit and significant adverse effects, including ventricular arrhythmias. Istaroxime, a novel Na + /K + -transporting ATPase inhibitor, also stimulates SERCA2a activity, which would confer improved inotropic and lusitropic properties with less proarrhythmic effects. We investigated hemodynamic, electrophysiological and potential proarrhythmic and antiarrhythmic effects of istaroxime in control and chronic atrioventricular block (CAVB) dogs sensitive to drug-induced Torsades de Pointes arrhythmias (TdP). In isolated normal canine ventricular cardiomyocytes, istaroxime (0.3–10 μM) evoked no afterdepolarizations and significantly shortened action potential duration (APD) at 3 and 10 μM. Istaroxime at 3 μg/kg/min significantly increased left ventricular (LV) contractility (dP/dt+) and relaxation (dP/dt−) respectively by 81 and 94% in anesthetized control dogs (n = 6) and by 61 and 49% in anesthetized CAVB dogs (n = 7) sensitive to dofetilide-induced TdP. While istaroxime induced no ventricular arrhythmias in control conditions, only single ectopic beats occurred in 2/7 CAVB dogs, which were preceded by increase of short-term variability of repolarization (STV) and T wave alternans in LV unipolar electrograms. Istaroxime pre-treatment (3 μg/kg/min for 60 min) did not alleviate dofetilide-induced increase in repolarization and STV, and mildly reduced incidence of TdP from 6/6 to 4/6 CAVB dogs. In six CAVB dogs with dofetilide-induced TdP, administration of istaroxime (90 μg/kg/5 min) suppressed arrhythmic episodes in two animals. Taken together, inotropic and lusitropic properties of istaroxime in CAVB dogs were devoid of significant proarrhythmic effects in sensitive CAVB dogs, and istaroxime provides a moderate antiarrhythmic efficacy in prevention and suppression of dofetilide-induced TdP.